Réponses

2013-01-27T16:05:33+01:00

Bonjour,

il s'agit d'une équation du second degré.

         x²+10x=39

<==>x²+10x-39=0

 

\Delta = b²-4ac=10²-4*1*(-39)=256

x1=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-10-\sqrt{256}}{2}=\frac{-10-16}{2}=-13

 

x2=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-10+\sqrt{256}}{2}=\frac{-10+16}{2}=3.

2013-01-27T16:06:00+01:00

x² + 10x -39 = 0 =>  (x² + 10x + 25) - 64 = 0 => (x+5)² = 64

donc x+5 = 8                   ou x+5 = -8

            x = 3                    ou x = -13